Mobile-Based Augmented Reality for Digital Heritage: 3D Documentation of Sumenep Palace Architecture - Adhitama, Muhammad Satya; Putri, Debri Haryndia; Ramdlani, Subhan (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2025)
Despite significant physical deterioration and the absence of comprehensive digital documentation, Sumenep Palace remains an important architectural and historical heritage site. The goal of this paper is to propose a digital conservation scheme using augmented reality technology. The system integrates photogrammetry, LiDAR scanning, and manual measurements to produce accurate three-dimensional (3D) models. These models, freely available on Android devices, were implemented in an augmented reality (AR) application we developed, using marker-based (QR code) tracking. Testing showed object loading times ranging from 8 seconds to 11 minutes, depending on the number of models, highlighting the need to optimize geometry for mobile AR. The resulting program functions both as a conservation database and as an interactive, accessible tool for teaching history. This approach can serve as a replicable template for other heritage sites in Indonesia, while also demonstrating the potential of augmented reality as a means of protecting digital cultural assets.